PERAN PEMERINTAH DAERAH PADA PENANGANAN COVID-19 - Andiraharja, Diyar Ginanjar (Fakultas Politik Pemerintahan, 2020)
This study aimed to assess the strategies that have been implemented by the central and regional governments in handling COVID-19. There are ten regulations related to the research objectives that have been reviewed. The method applied is normative legal research. Second level data is used in this study. The literature reviewed is used to solve researchers' questions. From this study it was revealed that the local government was obliged to decide on the policies that had to be taken in handling COVID-19 with normal basic health service conditions. In the situation of the COVID-19 pandemic, the appropriate regulations were enacted not the Law on Regional Government, but the Law on Health Quarantine. The conclusion of this study, in the condition of public health emergencies there is uncertainty at the local government level, because with the decentralization in the field of health causes basic health service standards vary according to the commitment and fiscal capacity of local governments. Strengthening the role of local government is a major factor in overcoming COVID-19. Health services in the regions must be ensured by the central government to conform to the COVID-19 handling standard. With the current state of public health emergencies, it is hoped that the division of roles of the center and the regions will be expected to ensure the safety of citizens.